2021
DOI: 10.7324/japs.2021.110508
|View full text |Cite
|
Sign up to set email alerts
|

The protective effect of Scenedesmus dimorphus polysaccharide as an antioxidant and antiaging agent on aging rat model induced by D-galactose

Abstract: Premature skin aging occurs due to the increased formation of reactive oxygen species (ROS), which causes oxidative stress, DNA damage, and collagen degradation. This study investigates the protective effect of Scenedesmus dimorphus polysaccharides (SDP) as an antioxidant and anti-aging agent on an aging rat model induced by D-galactose (D-gal). This study used 48 male Wistar rats divided into six groups: (1) normal control, (2) polysaccharide control, (3) aging control induced by D-gal 0.25 mg/g bw/days, (4) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…As mentioned earlier, enhancing the growth of S. dimorphus through the optimization of growth parameters plays an important role in its better exploitation for various applications. For instance, S. dimorphusis expansively used in biodiesel production as its cell contains 90% of diesel and polysaccharides S. dimorphus are proven to have an anti-skin aging property in an animal model 18,19 . Therefore, the present study is necessary for the production of S. dimorphus for above mentioned applications.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As mentioned earlier, enhancing the growth of S. dimorphus through the optimization of growth parameters plays an important role in its better exploitation for various applications. For instance, S. dimorphusis expansively used in biodiesel production as its cell contains 90% of diesel and polysaccharides S. dimorphus are proven to have an anti-skin aging property in an animal model 18,19 . Therefore, the present study is necessary for the production of S. dimorphus for above mentioned applications.…”
Section: Discussionmentioning
confidence: 99%
“…Biological applications of S. dimorphus are immense, and their rich nutrients and bioactive compounds made them extensively used as nutraceuticals and food supplements. As a nutraceuticals, S. dimorphus helps in repairing bone marrow damage and Omega-3 polyunsaturated fatty acids present in S. dimorphus play a significant role in preventing and treating diabetes, hypertension, cancer, autoimmune and heart diseases 11 .…”
Section: Fig 1: Morphology S Dimorphous (Utex 1237) Cells Observed Un...mentioning
confidence: 99%
“…Hwang et al (2019) revealed that it protects cells against apoptosis triggered by superoxide by converting the compound to O 2 and peroxide. Armaini and Imelda (2021) showed that SOD can be increased by giving Scenedesmus dimorphus polysaccharides (SDP) at a dose of 0.8 mg/g BW. The administration of SDP can stimulate collagen synthesis, repair skin tissue, increase catalase activity, and reduce malondialdehyde better compared to vitamin E. Furthermore, SDP shows benefits as an antioxidant and antiaging agent.…”
Section: Group Auc Value Collagen Percentage Gain Level (%)mentioning
confidence: 99%
“…The content of folic acid and pigments that function as antioxidants from S. dimorphus can treat aplastic anemia in rats, by increasing blood hematological parameters and repairing bone marrow damage [17] . S. dimorphus contains betaglucan, which is an active immunostimulator and has beneficial effects as free radical scavengers, to reduce blood lipids [18] , and can also prevent skin aging [19] . S. dimorphus as a nutraceutical can treat degenerative neurons in Alzheimer's disease, Parkinson's disease, heart disease, cancer, and other degenerative diseases, such as diabetes, obesity, and anemia.…”
Section: Introductionmentioning
confidence: 99%